PENGEMBANGAN PLATFORM DIGITAL WISATA MEMANCING DI KOTA BANDA ACEH - Fhalefi Djazuli; Faisal Syahputra; Agus Naufal (JURNAL KREASI RAKYAT, 2025)
Banda Aceh City, known for its natural beauty has great potential in the tourism sector, including fishing tourism. Fishing activities not only serve as a hobby for many people, but can also serve as a major tourist attraction. This study aims to develop a digital platform that will provide information about fishing spots in the city of Banda Aceh, information about fishing shops, and bait shops that will be made in tabular form and displayed on the website. This study uses a qualitative descriptive research method, Data consists of primary and secondary sources including observations, interviews and literature studies, data analysis is arranged in tabular form and will be uploaded to the website. Data from bait shops, which shows that live shrimp is still a favorite bait, for anglers. Factors that influence consumer choices include: product quality, affordable prices, strategic locations, and recommendations from the fishing community. The digital platform is designed using WordPress CMS with four main features: homepage, fishing spots, fishing shops, and bait shops. All data is presented in the form of interactive tables and map visualizations to facilitate information access for users.